2020
DOI: 10.1177/1947603520959405
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Is Associated with Anterior Ankle Impingement After Isolated Autologous Matrix-Induced Chondrogenesis for Osteochondral Lesions of the Talus

Abstract: Objective To determine potential predictive associations between patient-/lesion-specific factors, clinical outcome and anterior ankle impingement in patients that underwent isolated autologous matrix-induced chondrogenesis (AMIC) for an osteochondral lesion of the talus (OLT). Design Thirty-five patients with a mean age of 34.7 ± 15 years who underwent isolated cartilage repair with AMIC for OLTs were evaluated at a mean follow-up of 4.5 ± 1.9 years. Patients completed AOFAS (American Orthopaedic Foot and Ank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“… 15 , 20 , 33 This finding supports the growing evidence of the negative effect of smoking after cartilage repair. 15 , 20 , 33 , 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 , 20 , 33 This finding supports the growing evidence of the negative effect of smoking after cartilage repair. 15 , 20 , 33 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…15,20,33 This finding supports the growing evidence of the negative effect of smoking after cartilage repair. 15,20,33,38 The following limitations have to be acknowledged. First, this is a retrospective study with its associated biases, including infrequently documented patient-reported outcome measurements, which did not allow for a comprehensive clinical outcome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to a previous report of AMIC for osteochondral lesions of the talus, especially high preinjury sporting level activity patients tend to not return to their previous level. 60 The following limitations have to be acknowledged. First, preoperative KOOS were unavailable and only 67.7% of preoperative Kujala scores were available as the study was retrospective in its design.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to a previous report of AMIC for osteochondral lesions of the talus, especially high preinjury sporting level activity patients tend to not return to their previous level. 60 …”
Section: Discussionmentioning
confidence: 99%